From Genes to Teeth: A Scoping Review on Dental Anomalies and Dentition Alterations in Genetic Syndromes - Nadia Syifa Amira; Inne Suherna Sasmita (Maranatha Christian University, 2025)
Introduction: Genetic disorders, resulting from specific gene mutations, often impair systemic growth and craniofacial development, with manifestations extending to the oral cavity. Many syndromes present with odontogenesis alterations, including tooth anomalies in morphology, size, number, enamel integrity, and eruption timing. These dental phenotypes may serve as an early diagnostic indicator for multidisciplinary care. Methods: A systematic search of PubMed, Scopus, and EBSCO was performed for studies published from January 2015 to June 2025. Of 184 records, 9 met the inclusion criteria. Results: Distinct syndrome-specific dental patterns were identified. Turner syndrome mainly associated with supernumerary teeth, while Otodental syndrome showed globodontia. Wolf–Hirschhorn syndrome revealed delayed eruption, microdontia, and agenesis. Down syndrome presented with agenesis and delayed eruption. Williams syndrome was characterized by microdontia and diastema, whereas Wilson’s disease showed dens invaginatus. PHACE syndrome presented root anomalies, Ehlers–Danlos syndromes showed enamel hypoplasia and dentin defects, and Blepharocheilodontic syndrome demonstrated tooth agenesis and conical teeth. These patterns correlated with mutations in odontogenesis-related genes. Discussion: Dental anomalies represent consistent phenotypic manifestations in genetic syndromes. Each syndrome exhibits distinct abnormalities, as specific mutations result in variations in morphology, size, density, growth, eruption, and overall development, thereby highlighting genotype–phenotype correlations. Dentition changes may serve as non-invasive diagnostic markers, with genetic insights guiding therapy. Conclusion: Dental anomalies and dentition alterations contribute a significant phenotypic component in many genetic syndromes. Their recognition, alongside genetic testing, can improve diagnostic accuracy and promote comprehensive interdisciplinary management. Further research should refine genotype–phenotype mapping to optimize interdisciplinary care. Key word: Dental anomalies, genetic syndromes, dentition changes, supernumerary teeth, hypodontia, dens invaginatus, craniofacial abnormalities.